FAKTOR YANG MEMPENGARUHI KEPATUHAN PAJAK UMKM DI SOLO RAYA - Widya Putri Purwanto; Nur Kholis (PROSEDING, 2022)
The decrease in the ratio of tax’s compliance has an effect on tax income. So the purpose in this research was to determine the effect of taxpayer’s environment, taxpayer’s age, taxpayer’s gender, and the modernization of the tax system on SME taxpayer’s compliance in Solo Raya. Sampling method used purposive sampling technique for 96 SME with the parameters of having a culinary enterprise in Solo Raya. The data source was from primary data through questionnaire then processed by using multiple linear regression analysis and processed using SPSS ver 19. The result shows that environment, age difference, gender, and the modernization of the tax system has significant effect on tax compliance. On the other hand, taxpayer’s environment, taxpayer’s age, taxpayer’s gender, and modernization of the tax administration system has significant effect simultaneously. Keywords: tax compliance, taxpayer’s environment, age, gender, modernization of the tax administration